Exploring the Contribution of Secularism Ideology to the Education System in Turkey - Marsudi, Nevi Asiska; Sassi, Komarudin (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This research analyzes the contribution of the ideology of secularism to the education system in Türkiye, highlighting significant changes since the Kemal Atatürk era until the present. Methodology: This study employs a literature review method to investigate the impact of secularism on Turkey’s education system. This approach involves gathering and analyzing a range of sources, including books, academic articles, and both national and international journals related to secularism. Main Findings: The findings of this research provide an understanding of the impact of secularism on the paradigm shift that was previously oriented towards religious values towards a modern secular education model that is more open to developments in science and technology. As well as increasing access to education for women and minority groups, the emergence of fierce debate regarding the role of religion in public life, in addition to the hopes for its development prospects in the contemporary era. Novelty/Originality of this study: This study provides a comprehensive analysis of secularism's impact on Türkiye’s education system, offering new insights into the evolution of secular policies and their effects on social and educational inclusivity. It contributes to the understanding of secularism's role in contemporary educational reform and debates on religion's place in public life.